Empirical evidence for large X-effects in animals with undifferentiated sex chromosomes - Dufresnes, Christophe; Majtyka, Tomasz; Baird, Stuart J E; Gerchen, Jörn F; Borzée, Amaël; Savary, Romain; Ogielska, Maria; Perrin, Nicolas; Stöck, Matthias (Scientific reports, 2016)
Reproductive isolation is crucial for the process of speciation to progress. Sex chromosomes have been assigned a key role in driving reproductive isolation but empirical evidence from natural population processes has been restricted to organisms with degenerated sex chromosomes such as mammals and birds. Here we report restricted introgression at sex-linked compared to autosomal markers in a hybrid zone between two incipient species of European tree frog, Hyla arborea and H. orientalis, whose homologous X and Y sex chromosomes are undifferentiated. This large X-effect cannot result from the dominance or faster-X aspects of Haldane's rule, which are specific to degenerated sex chromosomes, but rather supports a role for faster-heterogametic-sex or faster-male evolutionary processes. Our data suggest a prominent contribution of undifferentiated sex chromosomes to speciation.
Keywords: Y Chromosome; X Chromosome; chromozom Y; sexuální diferenciace; Male; Animals; Ranidae; mužské pohlaví; ženské pohlaví; Female; chromozom X; Sex Differentiation; zvířata